Intra-arterial Injection of Lidocaine as a Cell Sensitizer during Irreversible Electroporation - Pan, Feng; Vollherbst, Dominik; Do, Thuy; Ridder, Dirk; Pereira, Philippe L.; Kauczor, Hans-Ulrich; Macher-Göppinger, Stephan; Sommer, Christof-Matthias (Journal of vascular and interventional radiology, 2020)
Purpose - To investigate whether intra-arterial injection of lidocaine enhances irreversible electroporation (IRE) in a liver model. - Materials and Methods - Conventional IRE (C-IRE) and lidocaine-enhanced IRE (L-IRE) were performed in 8 pig livers. Protocol 1 (tip exposure and electrode distance of 2.0 cm each) and protocol 2 (increased tip exposure and electrode distance 2.5 cm each) were used. Animals were sacrificed 3 hours after IRE. Study goals included electrical tissue properties (eg, current, conductivity) during IRE, geometry of IRE zones analyzed using computed tomography and magnetic resonance imaging (eg, volume and sphericity index), degree of acute liver damage, and irreversible cell death analyzed using microscopy (hematoxylin and eosin staining and terminal deoxynucleotidyl transferase deoxyuridine 5-triphosphate nick end labeling). Statistical comparisons were performed using the paired t test and Wilcoxon test. - Results - All treatments were performed without adverse events. Electrical tissue properties were not significantly different between C-IRE and L-IRE. For protocol 1, the diameter of the largest sphere within the IRE zone was significantly larger for L-IRE than for C-IRE (25.0 ± 4.7 mm vs 18.4 ± 3.1 mm [P = .013]). For protocol 2, the volume of IRE zone was significantly larger for L-IRE compared with C-IRE (46.0 ± 5.4 cm3 vs 22.6 ± 6.4 cm3 [P = .018]), as well as the diameter of the largest sphere within the IRE zone (27.1 ± 2.2 mm vs 19.8 ± 2.3 mm [P = .020]). For protocol 1, a significantly higher degree of irreversible cell death was noted for L-IRE than for C-IRE (1.8 ± 1.0 vs 0.8 ± 1.0 [P = .046]). - Conclusions - Intra-arterial injection of lidocaine can enhance IRE in terms of larger IRE zones and an increase of irreversible cell death.
Gesehen am 03.06.2020